Competition and innovation: An experimental investigation - Dario Sacco; Armin Schmutzler (University of Zurich, Socioeconomic Institute, 2008)
The paper analyzes the effects of more intense competition on firms' incentives to invest in process innovations. We carry out experiments based on two-stage games, where R&D investment choices are followed by product market competition. As predicted by theory, an increase in the number of firms from two to four reduces investments. However, a positive effect is observed for a switch from Cournot to Bertrand, even though theory predicts a negative effect in the four-player case.
Keywords: C92; L13; O31; 330; R&D investment; intensity of competition; experiment; Innovation; Investition; Wettbewerbsstrategie; Test